PEDAGOGICAL PROBLEMS OF THE DEVELOPMENT OF GIFTED CHILDREN AND THE WAYS OF RESOLVING THEM - Avramkova, Irina (Revista Inclusiones, 2020)
The article discloses the process of developing complex pedagogical strategies for working with gifted children and outlines the perspectives of improving pedagogical theory and practice in this direction. The problems of spiritual and moral guidelines in solving the problems of gifted children, the processes of their social adaptation and socialization, and the consideration of individual psychological characteristics of every gifted child are examined. The resolution of these problems is associated with abandoning the traditional understanding of collectivity and group learning activities, which is in many ways incompatible with the pedagogical process that includes gifted children. The need for an initial focus on the individual development of these students which should precede their immersion in group learning activities and different types of creative and intellectual work. In this case, certain collectivity and its nature have to be greatly determined by the capabilities of gifted children themselves. The article also explores the possibilities of gifted children’s well-timed contact with the surrounding reality, which is necessary for their complete socialization and adaptation. Otherwise, as indicated in the article, there emerges the problem of gifted children developing hypertrophied egocentrism or underestimating themselves after facing real life and the need to correlate one’s existence with certain interactions with society. This objective is targeted in the article in the context of the psychological characteristics of different personality types of gifted children that have both theoretical and practical significance.